Hematological changes in anemic dairy calves treated with a hematinic complex - Roberto González-Garduño; Fleider Leiser Peña-Escalona; Rocío Hernández-Díaz; Carlos Luna-Palomera; Ema de Jesús Maldonado-Siman; Ever del Jesus Flores-Santiago; Alfonso J Chay-Canul (Veterinary World)
Background and Aim: Weaning is a critical period in calf development, particularly under tropical conditions where nutritional stress and parasitic infestations can precipitate anemia. Anemia compromises growth and survival; yet, few studies have evaluated the effectiveness of hematinic therapy in anemic calves before weaning in tropical systems. This study aimed to assess hematological responses in anemic dairy calves treated with a hematinic complex and to establish anemia thresholds based on hematological indices in healthy calves raised under tropical conditions.